Upaya Penyadaran Petani dalam Meningkatkan Kualitas Lahan melalui Pemanfaatan Limbah Pertanian untuk Mencapai Sistem Pertanian Bawang Merah Berkelanjutan - Cahyo Wulandari; Muhammad Afif Syaifurrahman; Tri Wulandani; Hema Malini (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
The use of synthetic fertilizers and pesticides in Tempel Village has exceeded the recommended limits. The continuous cultivation pattern of shallots and the minimal land management have also led to difficulties in controlling pests and diseases, as well as a decline in soil quality. Improving soil quality can be achieved through the application of organic materials. One source of organic materials can be obtained from agricultural waste. On the other hand, agricultural waste such as rice husks and straw are available in large quantities. Additionally, eutrophication has led to uncontrolled growth of water hyacinth in water bodies. Until now, the abundant agricultural waste and water hyacinth in Tempel Village have not been utilized effectively. This program aims to utilize agricultural waste for fertilizer and soil amendment, as well as to raise farmers' awareness of the importance of sustainable farming concepts. The methods used include field observations, focused group discussions, socialization, and training. The training program conducted for farmers includes the production of biochar and compost. Through this program, farmers understand the dangers of intensive farming systems with excessive use of synthetic fertilizers and pesticides. Farmers also learn how to produce biochar and compost from agricultural waste. Based on the activities carried out, it can be concluded that the abundant agricultural waste and water hyacinth can be utilized as fertilizer and soil amendments, contributing to the implementation of sustainable farming systems.